Analysis of Coating Loss from Coated Stainless Steel Orthodontic Wire - Arata Ito; Hideki Kitaura; Takahiro Noguchi; Fumitoshi Ohori; Itaru Mizoguchi (Applied Sciences, 2022)
The leaching of metal ions from orthodontic appliances into the oral cavity is problematic for metal-allergic patients. Non-metal orthodontic appliances, such as plastic and ceramic brackets and elastomeric materials, have been clinically used and are effective for treatment of metal-allergic patients. However, only a few types of orthodontic wire are available for use in patients with metal allergies, thus restricting the establishment of orthodontic force systems in these patients. Wire surfaces can be coated with various substances to prevent leaching of metal ions. However, detachment of the coating may occur during orthodontic procedures, resulting in metal ion leaching from the substrate material. This study was performed to examine the resilience of various types of coated stainless steel wire to low pH, bending, and brushing. Wire surface characteristics were examined by stereomicroscopy and scanning electron microscopy. The degree of coating detachment due to bending of the wire was quantified by determining the change in the amount of metal ions eluted from the site of the bend immersed in hydrochloric acid. Exposure of the substrate metal by brushing was investigated by energy dispersive spectrometry. The results indicated that polyethylene naphthalate (PEN)-coated wire is resilient to bending, while gold (Au)-coated and titanium nitride (TiN)-coated wires are resilient to brushing.